Modification of carbon nanotubes with fluorinated ionic liquid for improving processability of fluoro-ethylene-propylene. (February 2017) - Ma, Hongyang; Chu, Benjamin; Hsiao, Benjamin S.
Graphical abstract: Highlights: Fluorinated ionic liquid had been successfully prepared and employed to modify MWCNTs. Modified MWCNTs dispersed well in FEP matrix can improved its mechanical properties. F-IL-MWCNTs serve as both of plasticizer and reinforcing reagent in FEP nanocomposite. Abstract: Fluorinated ionic liquid (F-IL), 1-(3-perfluorooctylpropyl)-3-methylimidazolium bis(perfluoroethylsufonyl)amine, had been successfully prepared and employed to modify multi-wall carbon nanotubes (MWCNTs) for improving the processability of fluoro-ethylene-propylene (FEP). The thermally decomposed temperature of F-IL was higher than 350 °C measured by thermal gravimetric analysis (TGA) which indicated that the fluorinated ionic liquid could be suitable for melting blend with FEP (blending at 290 °C) by a twin-screw extruder. Through "cation-π" interaction between the imidazolium cation of F-IL and the graphene surface of MWCNTs, MWCNTs can be modified with F-IL and used as nanofillers to improve the dispersity of MWCNTs in fluorocopolymer FEP verified by SEM images of the FEP nanocomposite. The structural characterization and mechanical property of FEP nanocomposite during the deformation were investigated by tensile experiments and simultaneous time-resolved wide-angle X-ray diffraction (WAXD) and small-angle X-ray scattering (SAXS) techniques.